Determinant factors that affect pregnant women satisfaction on HIV AIDS screening - Almira Gitta Novika; Dewi Setyaningsih (Jurnal Kesehatan Ibu dan Anak, 2021)
HIV screening integrated into antenatal care can significantly increase satisfaction for pregnant women who are infected or not so that it can increase the awareness of mothers to do screening. Purpose of the research to determine the determinants of satisfaction of pregnant women on HIV AIDS screening. The type of research was explanatory research used mixed method with cross sectional approach. The sampling technique was total sampling. Data analysis using Chi Square test and logistic regression. There was a relationship between health worker communication (p = 0.002) and physical appearance (p = 0.002) and satisfaction with HIV AIDS screening. There was no relationship between the attitude of health workers (p = 0.15) and the skills of health workers (p = 1.00) with satisfaction on HIV AIDS screening. The most influential factor on the satisfaction of pregnant women in HIV AIDS screening is physical appearance with Exp (B) of 0.148 that means officers and health facilities with unsupportive appearance will show less satisfaction of respondents by 0.148 times greater than health workers and facilities who have good physical appearance. The most influential factor on the satisfaction of pregnant women in HIV AIDS screening is physical appearance.